Analisis Pendekatan Guru dalam Meningkatkan Nilai Gotong Royong Siswa Kelas V melalui Pembelajaran IPS di SDN Suratmajan - Muhammad Al Habib; Mutiara Saputri; Muhammad Maulana; Muhammad Imaduddin; Arif Mahya Fanny (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze teachers’ approaches in improving the value of mutual cooperation among fifth-grade students through Social Studies learning at SDN Suratmajan. This research was motivated by the importance of instilling mutual cooperation values in elementary school students amid the growing individualistic attitudes in students’ social environments. The research used a qualitative method with a case study approach. Data collection techniques were conducted through observation, interviews, and questionnaires. The research subjects consisted of the fifth-grade homeroom teacher and fifth-grade students at SDN Suratmajan. The results showed that the teacher applied cooperative learning approaches, habituation of teamwork, group activities, and the use of the surrounding environment as a learning resource to instill mutual cooperation values in students. The questionnaire results also indicated that most students demonstrated helping behavior, respected their classmates’ opinions, maintained classroom cleanliness together, and showed responsibility in group work. Therefore, the learning approaches implemented by the teacher were considered effective in improving students’ mutual cooperation values in Social Studies learning at SDN Suratmajan.